THE ROLE OF FOLKLORISM IN PRESERVING CULTURAL HERITAGE: A LITERARY PERSPECTIVE - Shakhlo Yakubova (Modern American Journals, 2025)
The article examines how folklorism serves as a significant tool in safeguarding cultural heritage within literary works. It explores how traditional folklore elements, such as myths, legends, proverbs, and folk tales, are reimagined and embedded in modern literature, enabling cultural values, beliefs, and traditions to be passed down to future generations. The study delves into the methods by which authors integrate folkloric motifs into their narratives, creating a bridge between the past and present. Through a comparative analysis of selected literary works from various cultures, the research highlights the impact of folklorism on preserving cultural identity and promoting intercultural understanding. The findings emphasize that folklorism is not merely a nostalgic reflection but a dynamic force that enriches contemporary literature while maintaining cultural authenticity.
Keywords: folklorism, cultural heritage, literature, tradition, identity, mythology, preservation.